PENGARUH PEMBERIAN TAMBAHAN PENGHASILAN PEGAWAI (TPP) TERHADAP PENINGKATAN KOMPETENSI, KINERJA DAN DISIPLIN PNS PROVINSI SULTENG - Djanggola, Derry B. (Social Humanity: Jurnal Ilmu Sosial dan Humaniora, 2018)
It is generally known, that in improving working ethic effectively, one organization includes local government has to focus to the basic needs of public servant. In providing the needs and the improvement of public servants’ welfare, it is needed a reward and compensation for their service which is given to organizations as a form of motivation given to public servant. As a consequence, Central Sulawesi Governance, compensation is given besides salary and allowance that has been attached for public servant as well as incentive form namely Additional Employee Income (TPP). The scheme has been run since 2015. As it is written in the Government Rules Number 1 Year 2017 about Additional Income for Public Servant. Providing TPP aims as effort in improving working ethics, discipline, service quality and public servant welfare. As a policy that has run for 3 year, and it has been planned in 2018, it certainly appears in mind about the influence from the implementation of this policy. This research aims to know and analyze the influence of providing TPP toward public servant competence improvement in Central Sulawesi, the influence of providing TPP in improvement of working ethic of public servant, and the influence providing TPP in improvement of public servant discipline. This research is conducted by using survey method to public servant as TPP recipients by spreading questionnaire to 98 respondents. The research result shows that providing TPP has influence toward improvement of Central Sulawesi public servants’ competence, working ethics, and discipline, and the discipline of Public Servant is a variable, which is influenced strongly by the existent of providing TPP policy.